The Impact of Medical Students on Bilateral Reduction Mammoplasty Procedure Time. Issue 1 (July 2017) - Liao, Albert; Hart, Alexandra Marie Lippert; Losken, Albert
Abstract : Background: Exposure to the plastic surgery department is an important experience for medical students interested in the field. However, the impact of medical students in the plastic surgery operating room has not been previously examined. The aim of this study is to understand whether the presence of medical students impacted overall procedure time and postoperative complications for bilateral reduction mammoplasties. Materials and Methods: A retrospective review was performed on all patients who underwent bilateral reduction mammoplasty from January 2010 to December 2015. Procedures were divided into operations with medical students present and operations without medical students present. Patient average operation time and average procedure time were analyzed. A 2-tailed t-test was used to compare times with statistical significance set at P less than 0.05. A multivariate regression analysis was performed to control for potential confounders. Results: A total of 157 patients underwent bilateral reduction mammoplasties. Seventy-five of these cases had at least 1 medical student present; 82 of these cases had no medical student present. Patient information was not statistically different between groups. The average total operative time was 150.32 minutes, and the average procedure time (skin-incision to skin-closure) was 109.15 minutes. The total operative time was significantly longer in procedures with medical students: 158.25 minutes versus 143.06 minutes in procedures without medical students ( P = 0.013). However, the total procedure time was not significantly longer: 113.95 minutes with medical students versus 104.75 minutes without medical students ( P = 0.096). There were no differences in perioperative complications and multivariate regression analysis showed no statistically significant confounders for the duration of surgery.